Evaluación de la capacidad antioxidante del aceite esencial de las hojas de Peperomia dolabriformis Kunth frente al radical 2,2-difenil-1-picrilhidrazilo - Bazán Salinas, Sergio Andres (2017)
The objective of the present research was to evaluate the antioxidant capacity of the essential acceptance of the leaves of Peperomia dolabriformis Kunth against the radical 2,2-diphenyl-1-picrylhydrazyl (DPPH*). This plant was collected in the Campana hill, Trujillo province, La Libertad region. The oil extraction was carried out by hydrodistillation and the identification of the major components was done by Gas Chromatography coupled to Masses (GC MS). In order to determine the antioxidant activity of the oils, the DPPH root trapping capacity was used: DPPH* radical entrapment capacity, the highest DPPH* Finding an IC50 of 20.36 mg / mL. This suggests that in the essential oil studied there are present hydrogen-donor compounds or electrons that can stabilize the cationic radical, which are limonene and 1,6-dimethyl-4-(propan-2-yl)- 1,2,3,4,4A,7,8,8A-octahydronaphthalen-1-ol.